You are what you eat: Sequence analysis reveals how plant microRNAs may regulate the human genome. (March 2019) - Kashani, Bahareh; Hasani Bidgoli, Mansoor; Motahari, Seyed Abolfazl; Sedaghat, Nafiseh; Modarressi, Mohammad Hossein
Abstract: Background: Nutrigenomic has revolutionized our understanding of nutrition. As plants make up a noticeable part of our diet, in the present study we chose microRNAs of edible plants and investigated if they can perfectly match human genes, indicating potential regulatory functionalities. Methods: miRNAs were obtained using the PNRD database. Edible plants were separated and microRNAs in common in at least four of them entered our analysis. Using vmatchPattern, these 64 miRNAs went through four steps of refinement to improve target prediction: Alignment with the whole genome (2581 results), filtered for those in gene regions (1371 results), filtered for exon regions (66 results) and finally alignment with the human CDS (41 results). The identified genes were further analyzed in-silico to find their functions and relations to human diseases. Results: Four common plant miRNAs were identified to match perfectly with 22 human transcripts. The identified target genes were involved in a broad range of body functions, from muscle contraction to tumor suppression. We could also indicate some connections between these findings and folk herbology and botanical medicine. Conclusions: The food that we regularly eat has a great potential in affecting our genome and altering body functions. Plant miRNAs can provide means of designing drugs for a vast range of health problems including obesity and cancer, since they target genes involved in cell cycle (CCNC), digestion (GIPR) and muscular contractions (MYLK). They can also target regions of CDS for which we still have no sufficient information, to help boost our knowledge of the human genome. Highlights: Edible plants have miRNAs in common in a broad range of species. Four plant miRNAs can match perfectly with the human CDS sequences. These miRNAs are able to target human transcripts involved in metabolism and body functions. Abstract : Nutrigenomic has revolutionized our understanding of how diet is able to affect the human body and alter the genomic functions. A growing body of literature has stated that orally-consumed miRNAs can survive the digestion and be absorbed by the cells to regulate their target genes. This finding is still a source of ongoing debates about the amount of miRNA that is needed to affect the gene regulation, but the feasibility of this process wouldn't matter if those exogenous miRNAs wouldn't have targets in the human genome. Therefore this study was designed to detect miRNAs of edible plants for which there were human target genes. The miRNAs of edible plants were studied using the PNRD database and those in common in at least four species were then selected. The vmatchPattern was used to identify targets which went through four levels of refinement: aligning with the whole genome, filtering for the gene regions, the exon sequences and finally with the CDS. Four plant miRNAs were finally selected that could be found in a versatile group of plants, from apple to tobacco. The selected miRNAs could match perfectly with 41 regions of the CDS and contained 22 different human transcripts. In-silico analysis of these miRNAs showed that they targeted genes involved in the metabolism (e.g. GIPR ), the heart (e.g. FLT1 ), the muscles (e.g. ACTA2 ) and the neurons ( GRM7-AS1 ), cell-cell adhesion ( MYLK ) and cancer progression (e.g. CCNC ). Two target transcripts were also identified for which there were no known genes. In conclusion, our study indicated how our everyday diet and especially plant miRNAs can affect and regulate different aspects of the body functions. These data can be used to justify the use of some folk remedies and help predict some regimens for certain health issues including cancer and obesity.